2013
DOI: 10.3109/10520295.2013.837509
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofPiper hispidinervumon spermatogenesis and histochemistry of ovarioles ofSpodoptera frugiperda

Abstract: The fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), not only damages crops, but controlling its population also requires synthetic insecticides, which leads to selection of resistant populations and environmental contamination. Essential oils are an alternative for controlling this insect. There are few studies of the effects of these oils on the insect's reproductive system. We evaluated the effects of the long pepper, Piper hispidinervum, essential oil on the gonads of the armywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
2
12
0
3
Order By: Relevance
“…The reduction in fecundity could be due to the direct effect of the EO on adults, to a disruption of reproductive behavior by compounds present in the EO, or a combination of the two process. Plant products/EOs can alter gametogenesis (Alves et al, 2014; Lemenih…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The reduction in fecundity could be due to the direct effect of the EO on adults, to a disruption of reproductive behavior by compounds present in the EO, or a combination of the two process. Plant products/EOs can alter gametogenesis (Alves et al, 2014; Lemenih…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(Piperaceae) [44] and Szygium aromaticum (L.) (Myrtaceae) in sublethal concentrations [45]. The biochemical profile of S. frugiperda larvae was also affected when exposed to sublethal dose of Cymbopogon winterianus Jowitt (Poaceae), disturbing the insect reproductive histophysiology [46].…”
Section: Physiological Responses To Insecticides Sublethal Doses/concmentioning
confidence: 99%
“…Engelman (1998) believes that even ovariol number is affected following insufficient feeding at younger stages and also exposed to secondary metabolites during its ovarial development. Birah et al (2010) and Alves et al (2014) working on clove and long pepper extract, observed a juvenoid like effect which altered S. litura and Spodoptera frugiperda Smith (Lep: Noctuidae) reproduction, respectively. Clove oil in their study reduced number of eggs and their viability has also been reported by Cruz et al (2016) in S. frugipedra.…”
Section: Discussionmentioning
confidence: 99%